The Role of Awareness in Community Health Development: A Systematic Review - Alshahrani , Mohammed Khaled Saad; Alrobaiy, Faisal Rezeq Aydh; Almalki , Mohammed Awadh Saeed; Alharthy, Salma Saeed Saad; ALotaibi, Faris Falah M; Al qurashi, Mashael Hamed Hamad; Alharthi, Muqbil Awadh Ruddah; Alharthi , Abed Ahmed Mohammed; Althobity, Taghreed Mishal Saleh; Alharthi, Ebtisam Ahmed (Journal of Ecohumanism, 2024)
Awareness plays a pivotal role in advancing community health by fostering informed decision-making and promoting healthier lifestyles. This systematic review examines the impact of awareness campaigns and interventions on community health development. Using a rigorous methodology, studies from diverse populations and regions were analyzed to explore the strategies, challenges, and outcomes of health awareness programs. The findings highlight the effectiveness of culturally tailored and inclusive approaches in addressing health disparities, improving health literacy, and driving positive behavior change. However, challenges such as resource limitations and cultural resistance persist. This review underscores the need for innovative and sustainable awareness initiatives to enhance community health outcomes and advocates for collaborative efforts among stakeholders to address gaps and optimize strategies.